RANCANG PLANT SISTEM SMART HOME DENGAN SENSOR PENDETEKSI KEBOCORAN GAS LPG - Nawang Wulan Siti Nuridha; Endah Budi Purnomowati; Ali Mustofa (Jurnal Mahasiswa TEUB, 2022)
Along with the development of technology and the high mobility of the Indonesian population, microcomputer devices have been widely used in various aspects of daily life. There is a prototype smart home system that makes it easy for a family or individual who has high mobility and also for those who have physical limitations. In this study, the authors are interested in making an LPG gas leak detector in a smart home system. The tool in the system plant detects LPG gas using the MQ-5 sensor, Arduino UNO, DC motor, servo motor and LoRa Dragino Shield Dragino Clone. All of these tools use the Arduino IDE to process tools that are set up on the Arduino UNO. This plant tool also uses a meander-line microstrip antenna in order to expand the range of sending and receiving data to the control system. By using the MQ-5 sensor as a detector of LPG gas levels and with a LoRa communication tool which will later be processed on the Arduino Uno. This plant tool has a servo motor and a DC motor to reduce the level of LPG gas in the air around the plant system. The parameter measured is the level of LPG gas in the environment around the plant system in the form of ppm units. The MQ-5 sensor must be calibra